Ellipse-line-ellipse source trajectory and its R-line coverage for long-object cone-beam imaging with a C-arm system - Yu, Zhicong; Noo, F.; Lauritsch, G.; Dennerlein, Frank; Hornegger, Joachim (Medical Imaging 2012: Physics of Medical Imaging, 2012)
Over the last decade, significant progress has been made in terms of treatment of diseases using minimallyinvasive procedures. This progress was facilitated through multiple refinements of the imaging capabilities of C-arm systems in the interventional room, and more sophisticated procedures may become feasible by further refining the performance of these systems. Our primary focus is to eliminate two strong limitations of the current circular cone-beam imaging approach: cone-beam artifacts and limited extent of the volume covered in the direction of the patient bed. To solve this problem, we seek a source trajectory that (i) is complete in terms of Tuy's condition, (ii) can be periodically-repeated without discontinuities to allow long-object imaging, (iii) is practical, and (iv) offers full R-line coverage (an R-line is a line that connects any two source positions). A trajectory that satisfies all of our constraint is the Arc-Extended-Line-Arc(AELA) trajectory. Unfortunately, this trajectory does not allow smooth, continuous scanning at reasonable dose. In this work, we propose a new data acquisition geometry: the Ellipse-Line-Ellipse (ELE) trajectory. This geometry satisfies all of our constraints along with the attractive feature that smooth, continuous scanning at reasonable dose is enabled. © 2012 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).